A simple method for measuring electron drift velocity in gases using grid ionization chamber. (February 2021) - Zhang, Qingmin; Chen, Haizheng; Fan, Ruirui; Yi, Han; Gao, Keqing; Shao, Zhuang; Wei, Guangyou
Abstract: A simple method for measuring the electron drift velocity in gases with a given electric field using a grid ionization chamber is proposed and demonstrated. By collimating incident α particles that are perpendicular to the electric field, the drift velocity can be derived easily using the electron drift distance from primary ionization to a grid divided by the time interval between the cathode and anode signal starting times. These experimental settings can avoid additional signal processing of signals and reduce the effect of electron diffusion. Using this method, the measurement of electron drift velocities in 90% Ar + 10% CO2 is presented. Measured results agree well with the simulated values and with existing experimental results. Highlights: It is proposed to use a collimated beam of alpha particles to measure the drift velocity in a grid ionization chamber. The use of a collimator avoids the need for additional signal processing and reduces the effect of electron diffusion. Only a smoothing algorithm with a five-point approximation is needed. Obtained results agree with other measurements and simulations for a drift tube.